The Martin Marprelate Tracts (1588–89) and the Popular Voice - Black, J. L. (History compass, 2008)
The Martin Marprelate Tracts (1588-89), long regarded as some of the finest and most influential Elizabethan prose satires, have recently played a justifiably key role in discussions of pamphlet warfare, libel, late sixteenth-century communication practices, and the development of an early modern English public sphere. This article argues that the primary aim of the Marprelate project was to create a polemic that would generate and legitimate popular discussion of controverted issues. Evidence that the project succeeded in this aim is more elusive, but local examples of ‘Martinism’ in action do exist, and the wave of hostile response they generated reveals that the Marprelate tracts shaped contemporary perceptions of both the dangers and the possibilities of a public sphere - even if that sphere might not yet have fully existed.